A girl of the Limberlost - Stratton-Porter, Gene, 1863-1924 (Library of Indiana classics., 1984)
Deeply wounded by her embittered mother's lack of sympathy for her aspirations, Elnora finds comfort in the nearby Limberlost Swamp, whose beauty and rich abundance provide her with the means to better her life.